Optimizing Mist-Based Ablution: A Comprehensive Study of Water Distribution and Conservation Using Watercolour Visualization and Thermal Imaging Techniques - Embong, Abd Halim; Mohd Nor, Firdaus; Abdul Hamid, Syamsul Bahrin (International Journal of Integrated Engineering, 2023)
Conducting ablution constitutes a prerequisite for Muslims prior to engaging in prayer. This ritualistic practice involves the cleansing and wiping of specific body parts, including the hands, face, arms up to the elbows, head, and feet. Ensuring comprehensive water coverage of the aforementioned areas is a crucial criterion during ablution. However, excessive water consumption often occurs when Muslims perform ablution to achieve full coverage. Consequently, a more ecologically sustainable approach to ablution is necessary to minimize water wastage. A proposed water mist spray device aims to optimize water usage while adhering to the Islamic jurisprudence requirements of complete water coverage on ablution parts. To assess water coverage using the mist spray, an evenness distribution profile is employed through atomized mist colorization on paper and thermal imaging of ablution parts. An appropriate spray nozzle is chosen based on an analysis of spray distribution and coverage patterns on the target surface, utilizing image processing techniques. The proposed methodology involves mixing water with red watercolour and manually pumping it through the selected nozzle using an off-the-shelf water sprayer, thereby atomizing the coloured water to stain white paper. Subsequently, the paper is converted into a digital image and analysed using ImageJ software to determine the mist spray coverage percentage, spatial spread at various distances, and the extraction of stain and droplet sizes. This technique is applied to different types and sizes of spray nozzles to identify the most suitable nozzle for the prototype. The findings demonstrate that nozzles with smaller exit holes and higher water pressure yield more extensive spray coverage on the target surface. Upon selecting the appropriate nozzle, a Portable Ablution Mist Spray Device prototype is employed to evaluate water coverage for the ablution body parts. Thermal images of the ablution parts are captured before and after the ritual, with the temperature differences being analysed. The thermal images reveal a comprehensive and uniform spray distribution on the ablution body parts, accompanied by a temperature difference ranging from 0.9°C to 3.8°C among various participants.